2011
DOI: 10.1016/j.mrfmmm.2011.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent cells resemble embryonic stem cells demonstrating enhanced levels of DNA repair and efficacy of nonhomologous end-joining

Abstract: To maintain the integrity of the organism, embryonic stem cells (ESC) need to maintain their genomic integrity in response to DNA damage. DNA double strand breaks (DSBs) are one of the most lethal forms of DNA damage and can have disastrous consequences if not repaired correctly, leading to cell death, genomic instability and cancer. How human ESC (hESC) maintain genomic integrity in response to agents that cause DSBs is relatively unclear. Adult somatic cells can be induced to "dedifferentiate" into induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 50 publications
(78 reference statements)
3
53
0
Order By: Relevance
“…39 However, recent studies in human ESC and iPSC suggest that this may be different in humans and both HR and NHEJ have a key role in repair of DSBs with specific roles at different stages of cell cycle progression. 27,28 Our results discussed in this manuscript suggest that this is indeed the case for impairment of NHEJ-mediated-DSB repair in human iPSC results in accumulation of DSBs, enhanced apoptosis and increased genomic instability, despite the existence of a functional HR in these cells. On a more practical level, our study raises interesting questions on the ability of iPSC and more broadly embryonic and adult stem cells to preserve their genome integrity during ex vivo expansion.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…39 However, recent studies in human ESC and iPSC suggest that this may be different in humans and both HR and NHEJ have a key role in repair of DSBs with specific roles at different stages of cell cycle progression. 27,28 Our results discussed in this manuscript suggest that this is indeed the case for impairment of NHEJ-mediated-DSB repair in human iPSC results in accumulation of DSBs, enhanced apoptosis and increased genomic instability, despite the existence of a functional HR in these cells. On a more practical level, our study raises interesting questions on the ability of iPSC and more broadly embryonic and adult stem cells to preserve their genome integrity during ex vivo expansion.…”
Section: Discussionmentioning
confidence: 70%
“…These findings point to NHEJ as the main repair pathway used by human pluripotent stem cells to repair DNA damage caused by IR, corroborating previous findings. 27,28 Overexpression of DNA LIGASE IV restores NHEJ activity ( Figure 3a) and the ability to respond to IR, albeit not to the same extent as the wild-type control cells (Figures 3b-d).…”
Section: Nhdf-ipsc Controlmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent study demonstrated that iPSCs (Armstrong et al, 2010), which are similar to ESCs, maintain genomic stability by elevated non homologous end joining (NHEJ) activity and DNA repair efficacy (Fan et al, 2011). Notably, Parp1 and PARylation have been linked to the regulation of chromatin remodeling and genome stability (Deng, 2009).…”
mentioning
confidence: 99%